Tinjauan Hukum Ekonomi Syariah: Akad Mudharabah dalam Simpanan Ijabah di KSPPS Tamzis Bina Utama Cabang Purbalingga - Risky Lestari; Akhmad Nurasikin; Iman Fadhilah; Tri Handayani (Hukum dan Dinamika Masyarakat, 2024)
Ijabah savings is one of the term savings products at KSPPS Tamzis Bina Utama Purbalingga Branch. Many people around Purbalingga who conduct ijabah savings transactions without knowing the details of the contract used in it, people only know the extent of saving money for some time and getting benefits from these deposits. The purpose of this study is to describe the management practice of ijabah savings at KSPPS Tamzis Bina Utama Purbalingga Branch and to know the Islamic law review of ijabah savings at KSPPS Tamzis Bina Utama Purbalingga Branch. The data collection process is carried out by: Observation, Interview, Documentation. This research uses field research (Field Research) with a qualitative approach. The results of this study indicate that the Ijabah Saving Management Practice by KSPPS Tamzis Bina Utama Purbalingga Branch must first become a member at KSPPS, open a Pearl account then a new Ijabah Saving account with a mudharabah muthlaqah contract. In the management process between KSPPS and members are mutually beneficial. In Islamic law, the contract used in ijabah savings is mudharabah muthlaqah, this contract is permitted and is in accordance with the verses of the Qur'an, hadith, the views of the scholars and also DSN fatwa Number 03/DSN-MUI/IV/2000 concerning deposits and Number 115/DSN-MUI/IX/2017 concerning mudharabah contracts.